Political Background of Islamic Educational Institutions and the Reach of the Stage in Southeast Asia - Kohno, Takeshi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
The school taught terrorisms this paper asserts that examining madrasahs in the context of